SYNTHESIS OF FE(III)-SALEN AS A SUPEROXIDE DISMUTASE MIMIC - TUTI ADI NINGSIH NIM:10512072, DIEGOS
Metal complexes formed by transition metals and Schiff base ligands are best known for their applications in biomedic, biomimetic, and catalytic system. In this research, the potential of Fe(III)-salen complex as SOD mimetics was studied. Superoxide dismutase is a metalloenzyme that converts superoxide radicals (O2.(rumus)) to hydrogen peroxide (H2O2) and oxygen (O2). Salen compound has been synthesized from salicylaldehyde and ethylenediamine (2:1). It has a melting point of 121-122oC. Infrared spectrum of salen compound showed vibration from C=N bond at 1637 cm-1 which is the special characteristic of a Schiff base ligand. The 1H NMR spectrum of salen compound gave signals at the chemical shifts of 6,82-7,26 ppm and 8,35 ppm which are originated from H atom of aromatic and HC=N groups. Fe(III)-salen complex was synthesized from Fe(NO3)3.9H2O and salen with 1:1 ratio. The mass spectrum of the complex showed that its molecular weight was 323,16 g/mole which matched with the molecular formula of [Fe(C16H14N2O2]+. Its UV/Vis spectrum showed maximum absorbancy at 260 nm and 335 nm which indicated the d-dÃ‚Â’ transition. Fe(III)-salen is a paramagnetic compound with the ?eff of 5,66 BM. The SOD bioactive assay using non-enzymatic NBT/riboflavine method showed IC50 value at 2,98 ?M. Therefore, Fe(III)-salen have the potential as SOD mimetics.